The analysis of Denotative and Connotative Meaning in Ariana Grande’s Song Lyrics: A Semantic Study - Desy Riana Pratiwi; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Hasanuddin University, 2020)
The meaning in language is indeed diverse in types, one branch of linguistics that studies about meaning is semantic science. Semantic referred to as the study of meaning, this research aims to analyze denotative meanings and connotative meanings contained in song lyrics, an expression of one's feelings or ideas usually expressed through song lyrics. The song chosen for this research data is Ariana Grande's song entitled